Testing bronchodilator responsiveness. Issue 6 (5th December 2019) - Janson, Christer; Malinovschi, Andrei; Amaral, Andre F.S.; Accordini, Simone; Bousquet, Jean; Buist, A. Sonia; Garcia-Aymerich, Judith; Gnatiuc, Louisa; Tan, Wan; Torén, Kjell; Zuberbier, Torsten; Burney, Peter
We thank M.R. Miller for his comments on our paper regarding bronchodilator reversibility in asthma and COPD [1]. We agree that it is important to look at different ways of defining bronchodilator reversibility. In our analysis, we investigated both flow-related bronchodilator reversibility, defined by the change in forced expiratory volume in 1 s (FEV1 ), and volume-related bronchodilator reversibility, defined by the change in forced vital capacity. We also looked at both the change in lung function parameters expressed as percent of the baseline value and the change in FEV1 standardised by the subject's predicted value. The latter was evaluated to control for the sex, age and height dependency of lung function. The results when reversibility was expressed as percent of the predicted value (in supplementary tables E3 and E4) [1] were the same as when reversibility was expressed as percent of the baseline value. Our interpretation was therefore that, in the present study, neither flow-related nor volume-related bronchodilator reversibility were independently associated with the symptom burden, health status or dyspnoea in the COPD population. Neither flow-related nor volume-related bronchodilator reversibility were independently associated with the symptom burden, health status or dyspnoea in the COPD population http://bit.ly/2rigD1r